2018
DOI: 10.1111/jocn.14229
|View full text |Cite
|
Sign up to set email alerts
|

The experience of men and women with cystic fibrosis who have become a parent: A qualitative study

Abstract: These findings can inform health professionals to support the adaptive work necessary for families that include members with cystic fibrosis. A contemporary understanding of this phenomenon is necessary for facilitating clinically relevant communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(48 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…A total of 2335 resources were screened with 31 resources meeting our eligibility criteria. Using the inclusion criteria presented in Figure 1, 10 articles (Barker et al, 2017; Bianco et al, 2019; Cammidge et al, 2016; Duguépéroux et al, 2006; Hailey et al, 2019; Jessup et al, 2018; Schechter et al, 2013; Ullrich et al, 2015a, 2015b, 2015c) and three abstracts were retained (Downey et al, 2015; Frankl and Hjelte, 2004; Lauritsen and Pressler, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2335 resources were screened with 31 resources meeting our eligibility criteria. Using the inclusion criteria presented in Figure 1, 10 articles (Barker et al, 2017; Bianco et al, 2019; Cammidge et al, 2016; Duguépéroux et al, 2006; Hailey et al, 2019; Jessup et al, 2018; Schechter et al, 2013; Ullrich et al, 2015a, 2015b, 2015c) and three abstracts were retained (Downey et al, 2015; Frankl and Hjelte, 2004; Lauritsen and Pressler, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were European (Barker et al, 2017; Bianco et al, 2019; Cammidge et al, 2016; Downey et al, 2015; Duguépéroux et al, 2006; Frankl and Hjelte, 2004; Lauritsen and Pressler, 2008; Ullrich et al, 2015a, 2015b, 2015c), four studies were conducted in the United Kingdom (Barker et al, 2017; Bianco et al, 2019; Cammidge et al, 2016; Downey et al, 2015), and half used qualitative designs (Barker et al, 2017; Cammidge et al, 2016; Downey et al, 2015; Hailey et al, 2019; Jessup et al, 2018). Three articles described different parts of a larger study, using the same sample (Ullrich et al, 2015a, 2015b, 2015c) or a portion of the larger sample (Ullrich et al, 2015a, 2015b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,12,14,15 The only known study on CF-related reproductive health education including men suggests that deficiencies also exist in education from CF care teams on these topics. 13 The few published studies related to parenting with CF have demonstrated that individuals with CF face conflicting recommendations from CF providers, [16][17][18] difficulty balancing responsibilities, 17,18 shifting priorities, [17][18][19] coping with parental stress in the context of illness, 18,20 and guilt about the impact of illness on children. 18,19 Within the extant literature, few published studies address male reproductive health and parenting concerns, and even fewer address individuals' decision-making with respect to parenthood.…”
Section: Introductionmentioning
confidence: 99%
“…13 The few published studies related to parenting with CF have demonstrated that individuals with CF face conflicting recommendations from CF providers, [16][17][18] difficulty balancing responsibilities, 17,18 shifting priorities, [17][18][19] coping with parental stress in the context of illness, 18,20 and guilt about the impact of illness on children. 18,19 Within the extant literature, few published studies address male reproductive health and parenting concerns, and even fewer address individuals' decision-making with respect to parenthood. To address these gaps, the objectives of this study were to describe the parenting and reproductive health concerns of parents and nonparents with CF, including men and women, and to identify the psychosocial and educational needs of individuals with CF who are considering parenthood or are parents.…”
Section: Introductionmentioning
confidence: 99%